Climate chamber study on thermal comfort of walking passengers at different moving speeds. (October 2022) - Jia, Xinyu; Wang, Jiahao; Zhu, Yingxin; Ji, Wenjie; Cao, Bin
Abstract: Walking, which is a common activity for passengers in airport terminals, has a considerable effect on passengers' thermal comfort. Previous studies have only focused on the effect of the metabolic rate (MET) on thermal comfort. However, the role of the relative air velocity during walking cannot be ignored. To factor this, 26 healthy male subjects underwent three sessions: walking at 2 km/h for 20 min, 4 km/h for 20 min, and alternating between walking and standing at five operative temperatures ( T op ) of 20, 23, 26, 28, and 30 °C in the current study. In addition, MET was measured in 25 healthy male subjects while standing and walking at 2 km/h, 4 km/h, and 5 km/h with a 5 kg bag. The results showed that walking speed affected the dynamic variations in subjective responses, thermal sensitivity, mean skin temperature (m T sk ), and MET. However, there were slight differences in the neutral T op ( T n ), the most comfortable T op ( T mc ), and the preferred T op ( T p ) between 2 km/h and 4 km/h. While alternating between walking and standing, T n, T mc, and T p decreased during walking and increased during standing. The difference between thermal sensation vote and predicted mean vote increased with the standard effective temperature, and the predicted neutral m T sk was lower than the actual m T sk value. For young males, the upper limit of the MET range for analysing the airflow cooling effect in ASHRAE Standard 55 could be extended to 2.25 met. Highlights: The comfort and physiological responses were obtained at various walking speeds. The effect of relative v on thermal comfort during walking was analysed. Thermal sensitivity and neutral T op were compared between different speeds. Inaccurate skin temperature calculations may cause a deviation between PMV and TSV.